2017
DOI: 10.1186/s12957-017-1172-x
|View full text |Cite
|
Sign up to set email alerts
|

PTK7 is a novel oncogenic target for esophageal squamous cell carcinoma

Abstract: BackgroundOverexpression of PTK7 has been found in multiple cancers and has been proposed to serve as a prognostic marker for intrahepatic cholangiocarcinoma. Its role in esophageal cancer, however, remains to be clarified. We hypothesize that PTK7 positively regulates tumorigenesis of esophageal cancer.MethodsWe examined PTK7 expression pattern in human esophageal squamous carcinoma by Oncomine expression analysis and by immunohistochemistry (IHC) staining. We knocked down PTK7 in two esophageal squamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…PTK7 knockdown decreased proliferation, survival, wound healing and invasion by inhibiting ERK, JNK, p38, Akt and FAK activation in ESCC TE-10 and TE-11 cells 4 . Overexpression of PTK7 induced cell proliferation and invasion and suppressed apoptosis in ESCC TE-5 and TE-9 cells 24 . Consistently, we found here that overexpression of PTK7 increased proliferation in PTK7-low ESCC TE-5 and TE-14 cells and that PTK7 knockdown decreased it in PTK7-high ESCC TE-6 and TE-10 cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…PTK7 knockdown decreased proliferation, survival, wound healing and invasion by inhibiting ERK, JNK, p38, Akt and FAK activation in ESCC TE-10 and TE-11 cells 4 . Overexpression of PTK7 induced cell proliferation and invasion and suppressed apoptosis in ESCC TE-5 and TE-9 cells 24 . Consistently, we found here that overexpression of PTK7 increased proliferation in PTK7-low ESCC TE-5 and TE-14 cells and that PTK7 knockdown decreased it in PTK7-high ESCC TE-6 and TE-10 cells.…”
Section: Discussionmentioning
confidence: 94%
“…There are several mechanisms by which PTK7 may influence cancer 19 21 . For example, PTK7 increases the proliferation, survival, migration, and invasion of cells and wound healing by activating ERK, JNK, p38, and NF-κB signaling pathways, whereas it decreases apoptosis by suppressing the activation of caspase-9 and -10 4 , 19 24 . PTK7 also increases angiogenesis through activation of KDR 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Oncomine database expression studies and immunohistochemistry (IHC) studies have shown that PTK7 is overexpressed esophageal squamous cell carcinoma (ESCC) and may interact with p53 and caspases [20]. Also, PTK7-targeted antibody-drug conjugates reduced the prevalence of tumor-initiating cells and had several anti-tumor effects, including the inhibition of angiogenesis and the stimulation of immune cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…A number of tumor antigens have been screened to be used for CAR T-cell therapy, among which, our previous study constructed a humanized protein tyrosine kinase 7-CAR through genetic engineering to perform genetic modification of lymphocytes ( Fig. 2 ) ( 39 ).…”
Section: Clinical Applications Of Car T-cell Therapymentioning
confidence: 99%